Making the Future : Occupations, Interventions, Empire and Resistance - Chomsky, Noam (London Penguin Books, 2012)
"Making the Future is the latest collection of essays from Noam Chomsky, one of our most vital and provocative voices of political dissent. Taking up the thread from 2007's Interventions, these penetrating and compelling articles examine numerous topics, including the financial crisis, Obama's presidency, WikiLeaks and the on-going conflicts in the Middle East. Restating and refining his commitment to democracy and finding inspiration in the popular uprisings of the Arab Spring, Making the Future is Chomsky's fiercely-argued and timely comment on a fast-changing world." from the publisher.
Include Index
Keywords: United States -- a